2020
DOI: 10.3389/fevo.2020.00191
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Plant-Soil Feedback in the Field: Meta-Analysis Reveals That Competition and Environmental Stress Differentially Influence PSF

Abstract: Past research on plant-soil feedbacks (PSF), largely undertaken in highly controlled greenhouse conditions, has established that plant species differentially alter abiotic and biotic soil conditions that in turn affect growth of other conspecific and heterospecific individuals in that soil. Yet, whether feedbacks under controlled greenhouse conditions reflect feedbacks in natural environments where plants are exposed to a range of abiotic and biotic pressures is still unresolved. To address how environmental c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 91 publications
(134 reference statements)
4
53
0
Order By: Relevance
“…However, the effect of the origin of soil communities became evident in the feedback phase of Experiment II, in line with a recent experiment that demonstrated that it can take between four and six months to reveal the effect of soil microbes on plant biomass (Wang et al 2019). Moreover, the origin of soil communities determined plant biomass production under drought, being in line with a recent meta-analyses, that suggests intensified plant-soil interactions under drought (Beals et al 2020). At the same time, a recent study has reported no differences in community-level biomass of range expanders between drought and ambient conditions (Manrubia et al 2019), which suggests that in communities, neighbouring plant species might reduce the intensity of plant-soil interactions during drought.…”
Section: Discussionsupporting
confidence: 86%
“…However, the effect of the origin of soil communities became evident in the feedback phase of Experiment II, in line with a recent experiment that demonstrated that it can take between four and six months to reveal the effect of soil microbes on plant biomass (Wang et al 2019). Moreover, the origin of soil communities determined plant biomass production under drought, being in line with a recent meta-analyses, that suggests intensified plant-soil interactions under drought (Beals et al 2020). At the same time, a recent study has reported no differences in community-level biomass of range expanders between drought and ambient conditions (Manrubia et al 2019), which suggests that in communities, neighbouring plant species might reduce the intensity of plant-soil interactions during drought.…”
Section: Discussionsupporting
confidence: 86%
“…Although this viewpoint means that soil pooling may be acceptable when the scope of inference of the experiment is limited to the sampled populations, rather than a broader regional population (Gundale et␣al ., 2019), this only highlights that researchers must be explicit about the rationale and interpretation of their soil pooling methods. Plant–soil feedback research still faces multiple challenges (van der Putten et␣al ., 2013), including experimental design and interpretation (Brinkman et␣al ., 2010; this study), predicting plant–soil feedback effects (De Long et␣al ., 2019; Wandrag et␣al ., 2020), translating findings from the laboratory to the field (Heinze et␣al ., 2016; Forero et␣al ., 2019), unravelling context‐dependency along abiotic and biotic gradients (Smith‐Ramesh & Reynolds, 2017; Beals et␣al ., 2020), and linking plant–soil feedbacks to plant evolution, coexistence, and population and community dynamics (ter Horst & Zee, 2016; Chung et␣al ., 2019; Kulmatiski, 2019). Our work contributes to addressing these challenges by demonstrating that soil sample pooling may be an effective approach for large‐scale, multispecies studies that test broad hypotheses about the drivers and consequences of plant–soil feedbacks, especially when time, space or budgets are limited (Cahill et␣al ., 2017; Gundale et␣al ., 2017; Teste et␣al ., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Germinating in sterile conditions is common practice for many greenhouse studies (Fry et al, 2018;Naylor et al, 2017;Zolla et al, 2013), yet because root exudates are in uenced by microbial crosstalk and differ in sterile conditions (Oburger & Jones, 2018;Sasse et al, 2018), it is likely that an initial period of growth in sterile conditions could alter root exudates and, in turn, the seedlings' effect on microbial interactions after transplanting. No studies to our knowledge have evaluated how germinating in sterile conditions affects later plant-microbial interactions, but this potentially confounding effect could contribute to issues with scaling results from greenhouse (sterile germination) to eld studies (germination in live soil) (Beals et al, 2020;Forero, Grenzer, Heinze, Schittko, & Kulmatiski, 2019).…”
Section: Discussionmentioning
confidence: 99%